2013
DOI: 10.1021/bm4006886
|View full text |Cite
|
Sign up to set email alerts
|

Cationic β-Lactoglobulin Nanoparticles as a Bioavailability Enhancer: Protein Characterization and Particle Formation

Abstract: Cationic β-lactoglobulin (CBLG) was developed as a bioavailability enhancer for poorly absorbed bioactives. At most 11 anionic amino acid residues of β-lactoglobulin (BLG) were substituted by ethylenediamine (EDA), resulting in a highly positive surface charge (zeta potential up to 39 mV at pH 7.0) and significantly increased surface hydrophobicity. These changes conferred CBLG with desirable water solubility and improved mucoadhesion by at most 252%, according to quartz crystal microbalance (QCM) study. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 62 publications
4
39
0
Order By: Relevance
“…This corroborates with earlier studies, which have shown similar trend of increasing zeta potential along with increase in liquid lipid concentration (Nayak et al, 2010). In all the formulations, zeta potential was high enough to stabilize the nanoparticles against aggregation (Teng et al, 2013). Addition of either artemether or lumefantrine has no effect on the zeta potential of the nanoparticles.…”
Section: Resultssupporting
confidence: 92%
“…This corroborates with earlier studies, which have shown similar trend of increasing zeta potential along with increase in liquid lipid concentration (Nayak et al, 2010). In all the formulations, zeta potential was high enough to stabilize the nanoparticles against aggregation (Teng et al, 2013). Addition of either artemether or lumefantrine has no effect on the zeta potential of the nanoparticles.…”
Section: Resultssupporting
confidence: 92%
“…b-Lactoglobulin (BLG) is a 162-residue globular protein, makes up approximately 60% of bovine whey protein (Matalanis et al, 2011;Teng et al, 2013). Because of its flexibility and amphiphilic nature, BLG serves as a natural carrier for various nutrients (Lefèvre and Subirade, 2003;Papiz et al, 1986;Kontopidis et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…These values were over 15 and 40 times higher than that of BLG nanoparticles (0.254), and they were considerably higher than that achieved by other biopolymers such as chitosan (Chayed & Winnik, 2007). According to our previous report, CBLG molecules also displayed higher mucoadhesion than did BLG (Teng, Li, Luo, Zhang, & Wang, 2013). However, it was noteworthy that the C-EDA and C-P600 nanoparticles showed 770% and 475% higher mucoadhesion than did their constituent molecules, although the former exhibited less positive surface charges than did the latter (Table 1).…”
Section: Mucoadhesionmentioning
confidence: 66%
“…CBLG was synthesized via an EDC-aided coupling reaction, and nanoparticles were prepared with BLG and CBLG by organic solvent desolvation, as previously described (Teng, Li, Luo, Zhang, & Wang, 2013). In brief, the coupling process was initiated by incubating BLG and cationizer (EDA or PEI) at pH 4.75 in the presence of EDC, and it was terminated after 4 h by adding sodium acetate buffer.…”
Section: Synthesis and Characterization Of Cblg Molecules And Nanoparmentioning
confidence: 99%